Corporate Social Responsibility and Earnings Management: Evidence from Vietnam - Thong Tien Nguyen; Nhi Phuong Doan; Hung Kim Vuong (Asian Academy of Management Journal, 2024)
Managers might use corporate social responsibility (CSR) to conceal their misbehaviours. One of these is the implementation of earnings management (EM), which could have serious effects vis-à-vis information disclosed to stakeholders. This study examined the relationship between CSR and EM in Vietnam using the Kinder, Lydenberg, Domini (KLD) scale on five aspects: community, diversity, employees, environment, and products. The results show that in the economic context of Vietnam, for the enterprises in the consumer goods and consumer services industries, those firms with higher CSR scores are more likely to engage in EM. This finding provides additional evidence on the relation between CSR and EM and contributes to streams of studies on earnings and CSR.